PELATIHAN PEMBUATAN TERANG BULAN DAN MEMASARKAN SECARA ONLINE DI GOFOOD - Miftah Rakhmadian; Hendra Syaputra; Haidar Fatya Rahmi; Rusdianan Ningsih; Nonoy Nois S.M. (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Covid-19 outbreak was the toughest moment paced by citizen of the world. Each country applied diffentent policies to overcome it. During covid-19 people’s mobility was limited. Therefore, this empacted many sectors; one of which was economic sectors. As many activities were done from home, there seemed to be new comsutive behavior among the consumers. This behavior, of course, led to the rapid development of online business in order to reach more consuments. This Civic Service aimed at to equip the society with particular skills to make terang bulan cake and to promote the cake in one of market place, that was Gojek. The workshop was conducted on Jalan Tirto Taruno, Kelurahan Landungsari, Kecamatan Dau, Kota Malang. The activities in this civic services covered three steps namely observation, planning, and action. The results of this activities showed that the participants were successfully executed the skills of producing Terang bulan cake and how to sell it through Gojek aplication